2018
DOI: 10.1038/s41598-018-22050-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutation of NGN3 Gene Disrupts Pancreatic Endocrine Cell Development in Pigs

Abstract: The domestic pig is an attractive model for biomedical research because of similarities in anatomy and physiology to humans. However, key gaps remain in our understanding of the role of developmental genes in pig, limiting its full potential. In this publication, the role of NEUROGENIN 3 (NGN3), a transcription factor involved in endocrine pancreas development has been investigated by CRISPR/Cas9 gene ablation. Precomplexed Cas9 ribonucleoproteins targeting NGN3 were injected into in vivo derived porcine embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…While a previous study has demonstrated that culturing young porcine islets for 20 days in a multistep differentiation media involving the use of 6 different agents, including oncostatin M, dexamethasone, nicotinamide, exendin‐4, TGF‐ß1, and thrombin, resulted in a 2‐fold increase in the composition of beta and alpha cells, Nec‐1 treatment alone in our study increased the proportion of beta, alpha, and delta cells by 2‐fold on both days 3 and 7 of culture . The transcription factor Ngn3 directs the differentiation of pancreatic precursor cells toward the development of endocrine cells, but is suppressed after final differentiation of endocrine cells . In accordance with the increase in the composition of mature endocrine cells with prolonged culture in both control and untreated islets, the level of Ngn3‐positive endocrine progenitor cells decreased with culture time in our study, indicating the development of mature endocrine cells from progenitor cells.…”
Section: Discussioncontrasting
confidence: 40%
“…While a previous study has demonstrated that culturing young porcine islets for 20 days in a multistep differentiation media involving the use of 6 different agents, including oncostatin M, dexamethasone, nicotinamide, exendin‐4, TGF‐ß1, and thrombin, resulted in a 2‐fold increase in the composition of beta and alpha cells, Nec‐1 treatment alone in our study increased the proportion of beta, alpha, and delta cells by 2‐fold on both days 3 and 7 of culture . The transcription factor Ngn3 directs the differentiation of pancreatic precursor cells toward the development of endocrine cells, but is suppressed after final differentiation of endocrine cells . In accordance with the increase in the composition of mature endocrine cells with prolonged culture in both control and untreated islets, the level of Ngn3‐positive endocrine progenitor cells decreased with culture time in our study, indicating the development of mature endocrine cells from progenitor cells.…”
Section: Discussioncontrasting
confidence: 40%
“…In an effort to test the utility of pXEN cells as nuclear donors, we performed SCNT with the pXEN cells used in the chimera assay (above), alongside previously published crossbred knock-out fetal fibroblasts (FF NGN3-/-) as controls (25). A total of 222 cloned embryos reconstituted from pXEN (Xnt pCOL1A:GFP #3-2, n=61) and FF (n=161) were co-transferred into two surrogate gilts to exclude confounding variables associated with recipient animals affecting the outcome.…”
Section: Generation Of Viable Cloned Offspring From Pxen Cells Via Scntmentioning
confidence: 99%
“…$ data obtained from our previous study. *NGN3 -/cells originated from our previous report25 . All the fetal fibroblasts and pXEN cells with the exception of NGN3 -/cells used as SCNT donors were derived from the same fetus (female Ossabow fetal fibroblast #6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Humans and pigs are omnivorous mammals with similar physiology and metabolic diseases, including diabetes mellitus and its complications, from diet-induced obesity, insulinopathy and bcell stress [9][10][11] . Recent experimental advances expand possible studies of pig pancreas development to include gain and loss-of-function genetics [12][13][14][15] , fetal surgery and immunomodulation 16 , and primary islet cell genetics 17 . Prior studies of pig pancreas development have largely relied on immunohistological survey of tissue cell types [18][19][20][21] .…”
mentioning
confidence: 99%